Study of the preferences of doctors and pharmacists regarding medicines for the treatment of diseases of the peripheral nervous system - T. S. Brytanova; T. P. Zarichna; A. S. Hotsulia; Yu. V. Shostak (Zaporozhye State Medical University, 2022)
The aim of the work is to assess the preferences of doctors and pharmaceutical workers regarding drugs for the treatment of diseases of the peripheral nervous system in order to optimize the medical supply of the population. Materials and methods. Data from the State Register of Medicines of Ukraine, Compendium-online, questionnaires of neurologists and pharmaceutical workers were used in this research. The search systematic, analytical, qualimetric, comparative, statistical analyses were used in the work. Results. The results of a survey of neurologists revealed that for the treatment of diseases of the peripheral nervous system (radiculopathy, radiculalgia) the most effective treatment regimen is that, which includes "Nucleo CMF Forte", "Celtican" and "Myelofan". The effectiveness and safety of the studied drugs were confirmed by qualimetric analysis. However, the results of consumer surveys showed that the latter prefer a treatment regimen that contains "Dicloberl", "Ketanov" and "Dexalgin". These drugs are the most irrational in terms of side effects and contraindications. For consumers, the importance of the pharmacological effect outweighs the effects on the body from the side effects of drugs. Conclusions. The study of the preferences of doctors and pharmacists regarding medicines for the treatment of radiculopathy and radiculalgia was conducted. The most rational treatment regimens are identified, the effectiveness of which is confirmed by the method of qualitative analysis.